AUTISTIZM TECHNOLOGIES TO ESTABLISH METHODS OF WORK WITH CHILDREN'S FIX SINDROMLI (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article - functioning children are enhanced with comprehensive fix, if it works out, a group of experts: psychiatrist, neurologist, psychologist, speech therapist, the head of music are enhanced in partnership with parents and will be more successful. But this process should be done with the help of parents on the work of specialists in one program. The child's individual development and the selection of programs for to work out what you need. Teachers set clear learning objectives, overall qonuniyat have to rely on the child's development, help you to solve the problems arising should. The teacher's main task is to attract the individual and the joint business of the child to adapt in society am'lumotlar more about lit.